Harnessing Unconventional T Cells for Immunotherapy of Tuberculosis - La Manna, Marco P.; Orlando, Valentina; Tamburini, Bartolo; Badami, Giusto D.; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2020)
Even if the incidence of tuberculosis (TB) has been decreaseover the last years, the number of patients with TB is increasing worldwide.The emergence of multidrug-resistant and extensively drug-resistant TB is making control of TB more difficult. Mycobacterium(M.)bovis Bacillus CalmetteGuérin vaccine fails to prevent pulmonary TB in adults and there is an urgent need for a vaccine that is also effective in patients with HIV co-infection. Therefore, TBcontrol may benefit on novel therapeutic options beyond antimicrobial treatment. Host-directed immunotherapies could offer therapeutic strategies for patients with drug resistant TB or with HIV and TB coinfection. In the last years, the use of donor lymphocytes after hematopoietic stem cell transplantationhas emerged as a new strategyin the cure of hematologic malignancies in order to induce graft-versus leukemia and graft-versus-infection effects. Moreover, adoptive therapy has proven to be effective in controlling CMV and EBV reactivation in immunocompromised patientswith ex vivo expanded viral antigen-specific T cells Unconventional T cells are a heterogeneous group of T lymphocytes with limited diversity.One of their characteristics is that antigen recognitionis not restricted by the classical major histocompatibility complex (MHC). They include cluster of differentiation 1(CD1)-restricted T cells, MHC-related protein-1-restricted mucosal associated invariant T (MAIT) cells, MHC class-Ib-reactive T cells and γ T cells. Because these T cells are genotype-independent, they are also termed “donor unrestricted”T cells. The combined features of low donor diversity and the lack of genetic restriction make these cells suitable candidates for T cell-based immunotherapy of TB.